Investigation and applications of current and novel sustainability sciences - DeRose, Katherine K., author; Quinn, Jason C., advisor; Marchese, Anthony J., committee member; Jathar, Shantanu, committee member; Peebles, Christie, committee member (Colorado State University. Libraries, 2020)
Engineering-based sustainable solutions are required to ensure continued access to energy, food and clean water for a growing population. Techno-economic analysis and life cycle assessment provide a means of evaluating emerging technologies to determine if they can economically and sustainably provide solutions to current and future resource demands. Concurrently, performance targets can be identified to help drive technology forward in a sustainable fashion. A major advantage of sustainability analyses is the ability to perform early-stage technology evaluation prior to intensive research investment. The application of these techniques can be applied to a variety of technologies including renewable bio-based fuels. It is also necessary to understand the limitations of these sustainability sciences to properly interpret analysis results. This work focuses on the applications of sustainability sciences to multiple technologies including foundational investigation of the methodology behind assessments. The first technology evaluation showcases the iterative nature and relationship between sustainability sciences and research for a novel biofuel conversion process using algae as a feedstock. The second technology evaluation seeks to improve sustainability metrics of the widespread corn-ethanol process; and is also used as a case study to identify limitations in current sustainability sciences. The final technology evaluation is a novel application of sustainability sciences to identify technology solutions for environmental disruptions. Microalgae has been a feedstock of interest for renewable fuels production, but the technology remains impeded due to high growth costs. Most research has been focused on increasing biomass productivity and lipid content and/or reducing capital and operation costs associated with traditional growth systems. An alternative approach is to consider an entirely new growth method; attached-growth systems. Sustainability modeling was used to identify the optimal processing opportunities for the production of renewable fuels from algae grown in this method through the use of economic and environmental analyses. Results indicated that ash reduction, energy intensive processing and high growth costs needed to be addressed to improve economic viability. A secondary effort focused on advancing the research and modelling to further refine results based on this focus. Results show minimum fuel selling prices ranging between $9.13 to $31.22 per gallon of gasoline equivalent, dependent on scenario and process assumptions. Sustainability analyses can also be applied to improve current technologies. Corn ethanol represents a mature technology with a long production history as a first-generation alternative fuel but has been widely criticized for high production costs and only marginal sustainability improvements over traditional petroleum-based fuels. One approach for improving these metrics is to focus on increased utilization of co-products through additional processing. Sustainability analysis results indicate an additional co-product fermentation process may be considered as a value-add for refiners but is dependent on economic and product market assumptions. This process was also used as a case study to explore how life cycle methodology affects environmental impact results. Life cycle assessment (LCA) results have a broad variability with well-to-pump results ranging between 42 to 210 g CO2-eq MJ fuel-1, dependent on co-product allocation methodology. This variability within the results can affect a product's ability to meet environmental standards, such as the Renewable Fuel Standard, and represents a critical area for improved methodological guidance. In addition to technology, sustainability sciences can also be applied to identify economically viable solutions for environmental disruptions such as harmful algae blooms (HAB's). HAB's affect both fresh and saltwater bodies around the world, causing a variety of environmental and economic damages to surrounding ecosystems and communities. The primary driver of HAB's is eutrophication, or excess nutrients in the water, and the principal approach to mitigating HAB's is reducing nutrients before they collect en masse downstream. Technology solutions can be employed to remove nutrients from waterways, but feasibility of technology deployment is dependent on the economic viability. Applications of sustainability sciences allows researchers to identify potential solutions to reduce HAB events which are both effective and economically viable. Results show that on average, Lake Erie communities lose $142 M (± $29M) year-1 from HAB's without mitigation. Use of attached-algae systems show an average savings of $12-42M per year from HAB mitigation and represent the most promising technology investigated. Attached-algae systems are the only nutrient reduction technology to show net-positive cash flow when compared with traditional nutrient removal systems. This research dissertation outlines tasks associated with the different applications of sustainability sciences. First, sustainability analyses are used to identify current research roadblocks associated with a technology and are used to identify optimal processing options and provide feedback to researchers to improve these metrics. Next, the tool set was adapted to a novel biorefining process and used to evaluate a value-add proposition for a current technology and showcase current limitations of LCA methodology. And finally, they were leveraged to create a framework for evaluating costs and benefits of technology adoption for pro-active mitigation of environmental disruptions.
Keywords: life cycle assessment; sustainability; eutrophication; techno-economic analysis; renewable fuels